Concepções dos acadêmicos do Curso de Pedagogia em relação à Matemática: as implicações da/na formação - Oliveira, Ana Carolina Nogueira (2011)
This work presents a discussion about the possibility of changing the concept of future teachers of the initial years of elementary school toward to Mathematics, when it is developed a different methodological approach to its teaching. We will go through a way that started with the observation of a group from the fourth semester of the Education Course Night of the Federal University of Pelotas in the time they enroll in the discipline of Educational Theory and Practice IV, with emphasis on Mathematics. We continue the methodological work in the discipline started in the 6th semester, when it was offered the discipline of Educational Theory and Practice VI. The developed experience was designed in order to expand the discussion on the Mathematics contents which are taught in the early years of the elementary school, based on the initial conceptions that students expressed in relation to this discipline. We aimed to challenge teachers to think and discuss the Mathematics in a different way which could include logic to their teaching and observe if this work would allow a change of concept of the future teachers towards mathematics. Through analysis of collected material was possible a theoretical reflection on the results and realize that a work that seeks a different relationship in the classrooms of this discipline, with teachers in training, could help them to have another conception in relation to mathematics, consequently have subsides to propose alternatives to the teaching of this subject.